Optimum grape pomace proportion in feedlot cattle diets: ruminal fermentation, total tract nutrient digestibility, nitrogen utilization, and blood metabolites - Vinyard, James R (J Anim Sci, 2021)
Because of its high content of polyphenolic compounds, the dietary inclusion of grape pomace (GP) in ruminant diets can reduce reactive nitrogen (N) and methane emissions and enhance the shelf life and beneficial fatty acids (FAs) content of meat. However, the dietary inclusion of GP beyond a threshold that is still to be determined for feedlot cattle can also compromise nutrient supply and, thus, growth performance. This study investigated the optimum proportion of GP in finishing cattle diets. Nutrient intake and apparent total tract digestion, ruminal pH and fermentation, estimated microbial protein synthesis, route of N excretion, and blood metabolites were measured. Six ruminally fistulated crossbred beef heifers (mean initial body weight ± SD: 714 ± 50.7 kg) were used in a replicated 3 × 3 Latin square with 21-d periods. Dietary treatments were 0%, 15%, and 30% of dietary dry matter (DM) as GP, with diets containing 84%, 69%, and 54% dry-rolled barley grain, respectively. There was a linear increase (P = 0.07) in DM intake and quadratic change (P ≤ 0.01) in neutral detergent fiber (NDF) intake. There was a quadratic change (P ≤ 0.04) in apparent total tract DM, NDF, and crude protein digestibility as dietary GP content increased. However, there were no treatment effects (P ≥ 0.18) on total ruminal short-chain FA concentration and duration and area pH < 6.2, 5.8, and 5.5. Although N intake did not differ (269, 262, 253 g/d; P = 0.33) across dietary treatments, feeding GP led to a tendency for a quadratic change (P ≤ 0.07) in ruminal ammonia-N and plasma urea-N concentrations. Total N excretion also changed (quadratic, P = 0.03) because of changes (quadratic, P = 0.02) in fecal N excretion as urinary excretion of N and urea-N did not differ (P ≥ 0.15) across treatments. Feeding GP led to quadratic changes (P ≤ 0.01) in fecal excretion of fiber-bound N. Microbial N flow and apparent N retention also changed (quadratic, P ≤ 0.04) as dietary GP proportion increased. In conclusion, responses to dietary GP proportion were mostly quadratic with indications that nutrient supply as reflected by changes in apparent total tract nutrient digestibility, microbial N supply, and apparent N retention could be compromised beyond a 15% dietary inclusion level.